Genome-wide identification of Lysin-Motif Receptor-Like Kinase (LysM-RLK) gene family in Brachypodium distachyon and docking analysis of chitin/LYK binding. (April 2019) - Tombuloglu, Guzin; Tombuloglu, Huseyin; Cevik, Emre; Sabit, Hussein
Abstract: Lysin-Motif Receptor-Like Kinase (LysM-RLK) family proteins have critical function in plant-microbe interaction. During infection, common peptide domain of these proteins, namely LysM, interacts with bacterial gylcans or fungal chitins which triggers; (1) plant immune responses, (2) plant defense responses, or (3) plant-microorganism symbiotic interactions. Since pathogenic diseases cause severe annual loss in cereals, a better understanding of the molecular basis of host-pathogen interactions is required to facilitate the development of new resistance strategies. Hence, this study focuses on LysM-RLK gene family in Brachypodium, a model plant to study cereal-pathogen interactions. Potential roles of the identified proteins during pathogen infection was assessed by digital gene expression analyses and protein modelling. We found that Brachypodium genome comprises of 11 LysM -RLK genes, which were further divided into four major groups, namely LYK (4), LysMe (2), LysMn (1), and LYP (4). They were mostly localized in plasma membrane and outer membrane (extracellular). BdLysMe genes were found to be tandem duplicated. Expression analyses showed that BdLYK2, BdLYK3, and BdLYK4 were up-regulated after Fusarium graminearum ( Fg ) infection. Modelling and docking analyses of BdLYK proteins with fungal chitin revealed two the most susceptible LYKs (BdLYK3 and BdLYK4) possibly having role in chitin recognition and induction of plant immune/defense responses. Results of this study can contribute to the understanding of plant-microbe interactions by assessing the structure and putative function of LysM-RLK proteins in Brachypodium, a model plant to study cereal-pathogen interactions. Highlights: Brachypodium genome comprises of 11 LysM -RLK genes. BdLysMe genes were found to be tandem duplicated. Fungal chitin and LYK interaction was modelled by docking analyses. BdLYK3 and BdLYK4 are the most susceptible LYKs for chitin perception.